Cистема керування автоматизованим вимірювальним комплексом для дослідження властивостей пористих матеріалів на базі нечіткого нейроконтролера - Смолянкін, Олег; Маркіна, Людмила (Видавництво Львівської політехніки, 2013)
Purpose. Development of hardware-software complex based on IR 5047-50 tensile machine, model building automated control systems elongation details, modeling and forecasting the behavior of porous materials under complex loading trajectories with the use of fuzzy logic. Design/methodology/approach. The authors reviewed the methods of deformation of structural materials neodnorodnyh and installation for studying deformation and strength properties of powder materials. The developed device for lifting strength and deformation characteristics of a tenzometric sensors. Constructed taruvalni dependence. Models of porous materials based on fuzzy logic. We recommend using the method of fuzzy logic to predict material behavior under complex loading paths. Findings. Developed a model plant and automated control systems of power load parameters, followed by registration of deformation characteristics using fuzzy logic Originality/value appropriate use of fuzzy logic method for modeling the behavior of porous materials.
Keywords: вимірювальний комплекс; кластерізція; нечітка логіка; ПІД-контролер; нейроконтролер